Effects of frog skin peptide temporin-1CEa and its analogs on ox-LDL induced macrophage-derived foam cells - Yang, Xue-Feng; Liu, Xin; Yan, Xiao-Yi; Shang, De-Jing (Frontiers in Pharmacology, 2023)
Purpose: Atherosclerosis (AS) is one of the most important pathological foundations of cardiovascular and cerebrovascular diseases with high morbidity and mortality. Studies have shown that macrophages play important roles in lipid accumulation in the vascular wall and thrombosis formation in atherosclerotic plaques. This study aimed to explore the effect of frog skin antimicrobial peptides (AMPs) temporin-1CEa and its analogs on ox-LDL induced macrophage-derived foam cells. Methods: CCK-8, ORO staining, and intracellular cholesterol measurements were used to study cellular activity, lipid droplet formation and cholesterol levels, respectively. ELISA, real-time quantitative PCR, western blotting and flow cytometry analysis were used to study the expression of inflammatory factors, mRNA and proteins associated with ox-LDL uptake and cholesterol efflux in macrophage-derived foam cells, respectively. Furthermore, the effects of AMPs on inflammation signaling pathways were studied. Results: Frog skin AMPs could significantly increase the cell viability of the ox‐LDL-induced foaming macrophages and decrease the formation of intracellular lipid droplets and the levels of total cholesterol (TC) and cholesterol ester (CE). Frog skin AMPs inhibited foaming formation by reducing the protein expression of CD36, which regulates ox-LDL uptake but had no effect on the expression of efflux proteins ATP binding cassette subfamily A/G member 1 (ABCA1/ABCG1). Then, decreased mRNA expression of NF-κB and protein expression of p-NF-κB, p-IκB, p-JNK, p-ERK, p-p38 and the release of TNF-α and IL-6 occurred after exposure to the three frog skin AMPs. Conclusion: Frog skin peptide temporin-1CEa and its analogs can improve the ox-LDL induced formation of macrophage-derived foam cells, in addition, inhibit inflammatory cytokine release through inhibiting the NF-κB and MAPK signaling pathways, thereby inhibiting inflammatory responses in atherosclerosis.